Tuning Active Metal Atomic Spacing by Filling of Light Atoms and Resulting Reversed Hydrogen Adsorption-Distance Relationship for Efficient Catalysis - Chen, Ding; Lu, Ruihu; Yu, Ruohan; Zhao, Hongyu; Wu, Dulan; Yao, Youtao; Yu, Kesong; Zhu, Jiawei; Ji, Pengxia; Pu, Zonghua; Kou, Zongkui; Yu, Jun; et al. (Nano-Micro Letters, 2023)
Precisely tuning the spacing of the active centers on the atomic scale is of great significance to improve the catalytic activity and deepen the understanding of the catalytic mechanism, but still remains a challenge. Here, we develop a strategy to dilute catalytically active metal interatomic spacing (dM-M) with light atoms and discover the unusual adsorption patterns. For example, by elevating the content of boron as interstitial atoms, the atomic spacing of osmium (dOs-Os) gradually increases from 2.73 to 2.96 Å. More importantly, we find that, with the increase in dOs-Os, the hydrogen adsorption-distance relationship is reversed via downshifting d-band states, which breaks the traditional cognition, thereby optimizing the H adsorption and H2O dissociation on the electrode surface during the catalytic process; this finally leads to a nearly linear increase in hydrogen evolution reaction activity. Namely, the maximum dOs-Os of 2.96 Å presents the optimal HER activity (8 mV @ 10 mA cm−2) in alkaline media as well as suppressed O adsorption and thus promoted stability. It is believed that this novel atomic-level distance modulation strategy of catalytic sites and the reversed hydrogen adsorption-distance relationship can shew new insights for optimal design of highly efficient catalysts. Highlights: 1 Density functional theory calculations indicates that interstitial B atoms can tune the atomic spacing of host metal Os and achieve a reversal hydrogen adsorption-distance relationship. 2 The structure–activity relationship between the spacing of active Os atoms and catalytic activity is established. 3 Prepared OsB2 with increasing dOs-Os of 2.96 Å presents the optimal hydrogen evolution reaction activity (8 mV @ 10 mA cm−2) and robust stability in alkaline media.